Desain Desain Market Rekonstruksi Bangunan Gedung Pasar Modern Grand Bangka City (GBC) Semabung Lama Kota pangkalpinang - Wawan Setia Budi; Ahmad Ardhi Rizki; Ananda Abdi Pratama; Yayuk Apriyanti; Endang S Hisyam (Universitas Bangka Belitung, 2023)
The development of a region is supported by the regional economy, one of which is the trade sector which is related to the market as a place for buying and selling transactions. Community interest, whether in their role as traders or buyers, is influenced by the facilities available in the market and the rental price of the place. The Grand Bangka City Modern Market in Selindung Lama Village has been a trade and business center for the past 12 years and the condition of the building is worrying. In order to arouse people's interest in visiting and carrying out buying and selling transactions, this modern market building needs to be reconstructed. As input for the Pangkalpinang City Government, a mock-up of the reconstruction of the Modern Market building was designed with facilities that could attract public interest. The method implemented is through preliminary stages, design stages and making mockups. With this model design, it becomes input for the Pangkalpinang City Government to reconstruct the Grand Bangka City Modern Market so that it can be reused by the community so that it can support the economy of Pangkalpinang City.